Synthesis and Downconversion Emission Property of Yb2O3:Eu3+ Nanosheets and Nanotubes - Chao Qian; Tianmei Zeng; Hongrong Liu (Advances in Condensed Matter Physics)
Ytterbium oxide (Yb2O3) nanocrystals with different Eu3+ (1%, 2%, 5%, and 10%) doped concentrations were synthesized by a facile hydrothermal method, subsequently by calcination at 700°C. The crystal phase, size, and morphology of prepared samples were characterized by X-ray diffraction (XRD) and transmission electron microscopy (TEM). The results show that the as-prepared Yb2O3 nanocrystals with sheet- and tube-like shape have cubic phase structure. The Eu3+ doped Yb2O3 nanocrystals were revealed to have good down conversion (DC) property and intensity of the DC luminescence can be modified by Eu3+ contents. In our experiment the 1% Eu3+ doped Yb2O3 nanocrystals showed the strongest DC luminescence among the obtained Yb2O3 nanocrystals.